Variables during swing associated with decreased impact peak and loading rate in running - Schmitz, Anne; Pohl, Michael B.; Woods, Kaitlin; Noehren, Brian (Journal of biomechanics, 2014)
When the foot impacts the ground in running, large forces and loading rates can arise that may contribute to the development of overuse injuries. Investigating which biomechanical factors contribute to these impact loads and loading rates in running could assist clinicians in developing strategies to reduce these loads. Therefore, the goals of our work were to determine variables that predict the magnitude of the impact peak and loading rate during running, as well as to investigate how modulation of knee and hip muscle activity affects these variables. Instrumented gait analysis was conducted on 48 healthy subjects running at 3.3m/s on a treadmill. The top four predictors of loading rate and impact peak were determined using a stepwise multiple linear regression model. Forward dynamics was performed using a whole body musculoskeletal model to determine how increased muscle activity of the knee flexors, knee extensors, hip flexors, and hip extensors during swing altered the predictors of loading rate and impact peak. A smaller impact peak was associated with a larger downward acceleration of the foot, a higher positioned foot, and a decreased downward velocity of the shank at mid-swing while a lower loading rate was associated with a higher positioned thigh at mid-swing. Our results suggest that an alternative to forefoot striking may be increased hip flexor activity during swing to alter these mid-swing kinematics and ultimately decrease the leg's velocity at landing. The decreased velocity would decrease the downward momentum of the leg and hence require a smaller force at impact.